2019
DOI: 10.1111/1751-7915.13496
|View full text |Cite
|
Sign up to set email alerts
|

Preventive antibiotic treatment of calves: emergence of dysbiosis causing propagation of obese state‐associated and mobile multidrug resistance‐carrying bacteria

Abstract: Summary In agriculture, antibiotics are used for the treatment and prevention of livestock disease. Antibiotics perturb the bacterial gut composition but the extent of these changes and potential consequences for animal and human health is still debated. Six calves were housed in a controlled environment. Three animals received an injection of the antibiotic florfenicol (Nuflor), and three received no treatment. Faecal samples were collected at 0, 3 and 7 days, and bacterial communities were profiled to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 86 publications
(122 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, the Salmonella infection after FFC pre-treated chicks had the had the highest relative abundance of Proteobacteria, which was known to be the potential pathogens of poultry and/or humans. The recent study showed that the orfenicol preventive treatment of calves showed a 10-fold increase in facultative anaerobic Escherichia spp, which a signature of imbalanced microbiota [78]. And Sáenz et al oral administration of orfenicol to the sh observed a shift in the gut microbiome towards well-known putative pathogens such as Salmonella, Plesiomonas, and Citrobacter [79].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Salmonella infection after FFC pre-treated chicks had the had the highest relative abundance of Proteobacteria, which was known to be the potential pathogens of poultry and/or humans. The recent study showed that the orfenicol preventive treatment of calves showed a 10-fold increase in facultative anaerobic Escherichia spp, which a signature of imbalanced microbiota [78]. And Sáenz et al oral administration of orfenicol to the sh observed a shift in the gut microbiome towards well-known putative pathogens such as Salmonella, Plesiomonas, and Citrobacter [79].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Salmonella infection after FFC pre-treatment chicks had the highest relative abundance of Proteobacteria, which is known to be potential pathogens of poultry and humans. A recent study showed that preventive treatment of calves with orfenicol resulted in a 10-fold increase in facultative anaerobic Escherichia spp, which is a signature of imbalanced microbiota [78]. Sáenz et al reported that oral administration of orfenicol to sh resulted in a shift in the gut microbiome towards well-known putative pathogens such as Salmonella, Plesiomonas, and Citrobacter [79].…”
Section: Discussionmentioning
confidence: 99%
“…One of these consequences is a disproportional increase in the abundance of specific bacteria that may carry mobile elements containing ARGs. The study by Dobrzanska and colleagues (2020) in Microbial Biotechnology correlates changes in gut microbiota composition, after preventive antibiotic therapy, with weight gain and disease in calves. In this work, calves treated with Florfenicol changed their gut microbiota composition with enrichment of a facultative anaerobe Proteobacteria (mainly E. coli ) and consequently of E. coli mobile‐mediated ARGs that provided resistance to other drugs not administered to the calves.…”
Section: Figmentioning
confidence: 99%
“…Antibiotic treated calves also showed an increase in body weight compared to the non‐treated group, although both groups followed the same diet. Authors propose that antibiotic treatment of healthy animals led to unbalanced, disease‐ and obese‐related microbiota, that promotes the growth of microorganisms carrying clinically relevant mobile ARGs, and potentially increasing the risk of transmission of antibiotic‐resistant bacteria to humans (Dobrzanska et al , 2020).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation